Evaluating the intensity of fire at the Acheulian site of Gesher Benot Ya'aqov-Spatial and thermoluminescence analyses. - Nira Alperson-Afil; Daniel Richter; Naama Goren-Inbar (PLoS ONE, 2017)
This manuscript presents an attempt to evaluate the intensity of fire through spatial patterning and thermoluminescence methodology. Previous studies of Layer II-6 Level 2 at the Acheulian site of Gesher Benot Ya'aqov suggested that hominins differentiated their activities across space, including multiple activities around a hearth reconstructed on the basis of the distribution of burned flint artifacts. A transect of ~4 m was extended from the center of the reconstructed hearth of Level 2 to its periphery in order to examine the intensity of fire. Burned and unburned flint microartifacts were sampled along this transect. The results of earlier and current thermoluminescence (TL) analysis demonstrate a general agreement with the macroscopic determination of burning, indicating that the possibility of misinterpretation based on macroscopic observations is negligible. The TL signal from flint microartifacts close to the hearth's center shows unambiguous signs of strong heating, whereas with increasing distance from the hearth the TL signal can be interpreted as a result of decreasing temperatures and/or shorter durations of exposure to fire in addition to a decreasing number of flints showing fire damage. Our study shows that TL analysis can identify some variation in fire intensity, which allows a more precise classification of burned flint microartifacts with respect to their heating history.